Association of bystander cardiopulmonary resuscitation and neurological outcome after out-of-hospital cardiac arrest due to drowning in Japan, 2013–2016. (August 2019) - Fukuda, Tatsuma; Ohashi-Fukuda, Naoko; Hayashida, Kei; Kukita, Ichiro
Abstract: Background: Early initiation of cardiopulmonary resuscitation (CPR) performed by bystanders is essential in patients with out-of-hospital cardiac arrest (OHCA) due to primary cardiac cause. However, evidence about the effect of bystander CPR on neurologically favorable survival after OHCA due to drowning is scarce and controversial. Methods: This nationwide population-based observational study using prospectively collected government-led registry data included patients with OHCA due to drowning who were transported to an emergency hospital between 2013 and 2016. The primary outcome was one-month neurologically favorable survival defined as Glasgow-Pittsburgh Cerebral Performance Category score of 1-2. The secondary outcomes were one-month survival and prehospital return of spontaneous circulation (ROSC). Results: The full cohort (n = 12, 139) comprised 6291 (51.8%) male patients, and the mean age was 73.7 (standard deviation [SD], 18.8). Of these, 5157 (42.5%) received bystander CPR, and 6982 (57.5%) did not. 4345 patients receiving bystander CPR were propensity-matched with 4345 patients not receiving bystander CPR. In the propensity score-matched cohort, bystander CPR was associated with increased chance of one-month neurologically favorable survival (0.4% vs. 0.8%; risk ratio [RR], 2.19; 95%confidence interval [CI], 1.21–3.95; P  = 0.0076), one-month survival (1.1% vs. 1.7%; RR, 1.55; 95%CI, 1.09–2.22; P  = 0.0150), and prehospital ROSC (2.7% vs. 3.5%; RR, 1.30; 95%CI, 1.03–1.65; P  = 0.0296). Similar association was observed across a variety of sensitivity analyses. In subgroup analysis, statistically significant difference was not observed in pediatric OHCA due to drowning, although the sample size was too small (n = 218). Conclusions: Among patients with OHCA due to drowning, bystander CPR was associated with increased chance of neurologically favorable survival.